Saṃghaʹ guiṇʻʺ krīʺ 9 guiṇʺ ʾa kroṅʻʺ - Moṅʻ Moṅʻ, Ūʺ (Ranʻ kunʻ : Praññʻ sūʹ ʾa laṅʻʺ cā pe, 1981)
About 9 kinds of Sangha gang.
Religious institutions, Myanmar
Keywords: Religious institutions -- Burma; Buddhism -- Burma